Where I am [compact disc, unabridged] : heaven, eternity, and our life beyond the now - Graham, Billy, 1918-2018 (Brilliance Audio, 2015)
'I will come back and take you to be with me that you also may be where I am.' John 14:3 Although Billy Graham may no longer preach from the stadiums of the world, in this book listeners will sense his heart still beats strong with the resounding assurance that he will spend eternity with Jesus Christ, the Savior of the world.